Bernard Lesfargues (1924-2018), entre fédéralisme européen et autonomisme occitan - Jean-Francis Billion (Lengas)
Borned and died in Périgord, Bernard Lesfargues (1924-2018) is a poet (French and Occitan), a translator (Spannish and Catalan), a publisher and a Federalist militant (European and World). He joined the IEO and engaged in politics (1945) but will decide to focus on his litterary and publishing activities after the founding of the Fédérop Library (1969), the Federop Publishing House (1975), and his retyrn in Périgord (1986).